Aflatoxin M1 in Brazilian goat milk and health risk assessment. Issue 4 (3rd April 2021) - de Matos, Clarisse J.; Schabo, Danieli C.; do Nascimento, Yuri M.; Tavares, Josean F.; Lima, Edeltrudes de O.; da Cruz, Paloma O.; de Souza, Evandro Leite; Magnani, Marciane; Magalhães, Hemerson I. F.
Abstract: Contamination of goat milk with aflatoxin M1 (AFM1 ) is a public health concern. This study investigated filamentous fungi in goat feed and quantified AFM1 in milk samples (n = 108) from goat fed forage and concentrate. Based on the detected AFM1 concentration, risk assessment analyses were performed concerning the Estimated Daily Intake (EDI) for one-year-old children and adults. Filamentous fungi were found in goat feed samples in a range of 3.1 ± 1.9 to 4.2 ± 0.2 log CFU/g. Five genera were identified, to cite Aspergillus, Penicillium, Fusarium, Rhizopus and Acremonium. Aspergillus species comprised A. flavus, A. niger, and A. ochraceus . All goat milk samples were contaminated with AFM1 (5.60–48.20 ng/L; mean 21.90 ± 10.28 ng/L) in amounts below the limits imposed by regulatory agencies. However, EDI values for AFM1 through goat milk estimated for one-year-old children were above the Tolerable Daily Intake. The calculated Hazard Index for one-year-old children indicated potential risk of liver cancer due to goat milk consumption. The Margin of Exposure values to AFM1 in one-year-old children and adults consuming goat milk as the unique milk source indicated increased health risk. Therefore, contamination of goat milk with AFM1 should be considered a high priority for Brazil's risk management actions.